Peningkatan Kemampuan Menggunakan Huruf Kapital melalui Metode Penugasan pada siswa Kelas V SDN Inti Tondo Palu - Ulfah Ulfah (Universitas Tadulako, 2015)
The problem in this research was whether the application of assignment method can improve the fifth grade students’ ability using the capital letters at SDN Inti Tondo Palu? The study aimed to improve the fifth grade students’ ability using the capital letters through the assignment method at SDN Inti Tondo Palu. The researh methodology used a descriptive method by applying the class action research with phases of planning, action, observation and reflection. The data collection technique was conducted by using observation and evaluation, while data analysis method through formulation of the classical and individual completeness as well as determine the students’ average score in each cycle. The results showed the average score of 6,07 was obtained in the first cycle and the average score of 9 was obtained in the second cycle. As a result the research was considered succeeded.